Comparison of flexural behaviors between plain and steel-fiber-reinforced concrete beams with hybrid GFRP and steel bars. (September 2022) - Lu, Chunhua; Cai, Qiming; Xu, Ke; Sha, Xin; Yan, Yongdong
Abstract: This study investigates the flexural behavior of steel-fiber-reinforced concrete (SC) beams with hybrid glass fiber reinforced polymer (GFRP) and steel bars. The experimental results of current SC beams are compared with those of the plain concrete (PC) beams conducted in our previous research. Taking account of the differences in nominal reinforcement ratio and reinforcement layout of seven tested SC beams, the test results including cracking load, ultimate load, failure mode, crack spacing and width, and mid-span deflection were firstly discussed. Then, a comprehensive comparison of flexural behaviors between SC beams and PC beams with same reinforcements was conducted in this paper. Especially, the crucial effects of type and strength of concrete on flexural capacity and failure mode of test beams were analyzed in detail. Finally, for concrete beams reinforced with hybrid (GFRP and steel) bars, the optimization of two balanced nominal reinforcement ratios was proposed to ensure the beam's flexural failure in an appropriate-reinforced mode without rupture of GFRP bars.